Effectiveness of Using Drops Application in English Vocabulary on Students’ Learning Outcomes - Sabilla, Sonia; Sholihatul Hamidah Daulay (ELLITE: Journal of English Language, Literature, and Teaching, 2025)
The study aims to determine the effect of using an English vocabulary learning application called "Drops" as a tool in helping English as foreign language. This app was designed to be installed into smartphones with Android and IOS System. This study uses a quasi-experimental design, with as many as 30 students in the experimental group who study with the Drops application and 30 students in the control group who use conventional textbook based learning methods. Data were collected through test vocabulary with pretest and post-test to assess the effect of the using this app on vocabulary learning in junior high school in Deli Serdang. The results of the statistical analysis showed that there was a significant increase in vocabulary learning outcomes in the experimental group compared to the control group (p<0.05). At the conclusion of the study, researcher realized that the use of the Drops application significantly improves students' vocabulary learning outcomes. The combination of gamification, visual learning, and micro-learning in Drops enhances engagement and retention, making vocabulary learning more effective and suggesting that digital applications can serve as valuable tools in language education.